2012
DOI: 10.1007/s10903-012-9650-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Drug Risk Behavior Pre- and Post-Emigration Among Latino Migrant Men in Post-Hurricane Katrina New Orleans

Abstract: High rates of sex and drug risk behaviors have been documented among Latino migrant men in the U.S. Whether these behaviors were established in the migrants’ home countries or were adopted in the U.S. has not been described and has implications for prevention strategies. Quarterly surveys were conducted to gather information on selected sex and drug risk practices of Latino migrant men who arrived in New Orleans after Hurricane Katrina seeking work. Both kappa scores and McNemar’s tests were performed to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
0
15
1
Order By: Relevance
“…Belonging to a social organization was found to be protective against multiple sexual partnerships, drug use, and binge drinking, which indicates that community support may play a protective role against engaging in high-risk behaviors (10). Another study of this population found the majority of these risk behaviors were adopted upon migration to the U.S. including patronage of a female sex worker, men having sex with men behavior and cocaine usage and that those living with family were less likely to engage in these risk behaviors (14). …”
Section: Introductionmentioning
confidence: 99%
“…Belonging to a social organization was found to be protective against multiple sexual partnerships, drug use, and binge drinking, which indicates that community support may play a protective role against engaging in high-risk behaviors (10). Another study of this population found the majority of these risk behaviors were adopted upon migration to the U.S. including patronage of a female sex worker, men having sex with men behavior and cocaine usage and that those living with family were less likely to engage in these risk behaviors (14). …”
Section: Introductionmentioning
confidence: 99%
“…As seen in the aftermath of Hurricane Katrina in Louisiana and Mississippi in 2005, PWID are particularly vulnerable to the effects of hurricanes (Bennett, Golub, & Dunlap, 2011; Mills, et al, 2009). Disruption of illicit drug markets can add to the difficulties in evacuating and obtaining food and shelter for PWID, and can lead to increased risks of transmission of HIV and other blood-borne infections (Bennett, et al, 2011; Mills, et al, 2009). Unfortunately, with ongoing global warming, climactic events such as storms, floods and droughts have increasing potential to exacerbate HIV epidemics through population displacement, trauma, service disruption and economic instability (Ebi, Kovats, & Menne, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies conducted with farmworkers, with whom Latino day laborers share similarities, have found that time spent in the United States was related to higher rates of depression (Vega, Kolody, Valle, & Hough, 1986; Vega, Scribney, Aguilar-Gaxiola, & Kolody, 2004). Although Latino day laborers do not seem to acquire drinking as a result of living in the U.S. (Mills et al, 2012) and generally report low rates of alcohol use, when they drink, they drink heavily (Mills et al, 2012; Organista & Kubo, 2005; Worby & Organista, 2007). …”
Section: Introductionmentioning
confidence: 99%